(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Zulkarnaen RN, Nisyawati, Witono JR. 2019. Population study and habitat preferences of Pinang Jawa (Pinanga javana) in Mt. Slamet, Central Java, Indonesia. Biodiversitas 20: 712-718. Conservation effort of Pinang Jawa is hampered due to lack of information on its ecology and population biology. The species is an endemic palm species to Java. The study aimed to assess the population study and habitat preference of Pinang Jawa in Mt. Slamet, Central Java. The research design used a purposive sampling method with a plot measuring 10x10 m. The observation plot was successfully made with a total of 183 plots. The result showed that the population was dominated by adult palm (mature) with the number of 1023 individuals on the southern slope of Mt. Slamet. Individuals growth dominated in hill slope. Population structure was dominated by individuals with stem heights of 6.1-8.1 m and stem diameters of 7-8.9 cm. The stem height and stem diameter class distribution showed that high mortality rate occurs in the seedlings stage class, although this stage should be high recruitment due to the seed production is perennial continuously. Predators were identified as the main threat for seedlings of Pinang Jawa. The result of statistical analysis clearly provides reveals that abiotic factors in which influencing the density of Pinang Jawa was slope, litter thickness, and crown cover.